2018
DOI: 10.1093/ejo/cjx104
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial morphology and growth in young patients with congenital or childhood onset myotonic dystrophy

Abstract: Young patients with DM1 had already from the beginning a more retrognathic profile and hyperdivergent skeletal aberration with a steep mandibular plane and large intermaxillary angle when compared with healthy individuals. The intermaxillary angle did not decrease during the observation period, contrary to what was observed in healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…12 In the study of Fontinha et al, it was represented that DM1 patients exhibited a retrognathic profile and a high prevalence of malocclusions. 17 The other findings of the present study were high prevalence of flat-shaped mandibular condyle (48.5%), high frequency of flattening (37.9%) among patients with DM1, and a statistically significant difference between DM1 and healthy controls according to the prevalence of osseous changes observed in the condyle. No significant difference was detected between gender and mandibular condyle morphology/ osseous changes observed in the condyle in both groups.…”
Section: Ta B L Esupporting
confidence: 61%
See 1 more Smart Citation
“…12 In the study of Fontinha et al, it was represented that DM1 patients exhibited a retrognathic profile and a high prevalence of malocclusions. 17 The other findings of the present study were high prevalence of flat-shaped mandibular condyle (48.5%), high frequency of flattening (37.9%) among patients with DM1, and a statistically significant difference between DM1 and healthy controls according to the prevalence of osseous changes observed in the condyle. No significant difference was detected between gender and mandibular condyle morphology/ osseous changes observed in the condyle in both groups.…”
Section: Ta B L Esupporting
confidence: 61%
“…Papaefthymiou et al specified that the increased prevalence of Class II malocclusion in patients with DM1 is quite possibly linked to the mandibular posterior rotation 12 . In the study of Fontinha et al, it was represented that DM1 patients exhibited a retrognathic profile and a high prevalence of malocclusions 17 …”
Section: Discussionmentioning
confidence: 99%
“…The craniofacial morphology of patients with DM1 is characterised by a retrognathic profile, large gonial angle, and a steep mandibular plane with a long lowerfacial height [10]. Young patients with congenital or childhood onset DM1 display an altered craniofacial morphology already at an early stage, which does not seem to improve during growth [11]. Malocclusions are common in both children and adults and previous studies have reported cases of class II occlusion, class III occlusion, anterior open bite and lateral cross-bite [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Young patients with congenital or childhood onset DM1 display an altered craniofacial morphology already at an early stage, which does not seem to improve during growth [11]. Malocclusions are common in both children and adults and previous studies have reported cases of class II occlusion, class III occlusion, anterior open bite and lateral cross-bite [10,11]. One theory that has been proposed to explain this appearance is that an open mouth posture with the mandible and tongue in a lowered position allows over-eruption of the posterior teeth, as well as stretching of the facial muscles, creating an imbalance between the intra-oral and extra-oral pressures [10].…”
Section: Introductionmentioning
confidence: 99%
“…Common features of muscular disorders are the increased vertical dimension of the face, expressed in the maxillofacial complex by compensatory overeruption of the posterior teeth and subsequent severe anterior and lateral open bite. Additionally, deviations in the transverse dimension of the maxilla are frequently present [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%